Playing towards Motivation: Gamification and University Students in Physical Activity! - Victor Javier Sotos-Martinez; Salvador Baena-Morales; Manuel Sanchez-De Miguel; Alberto Ferriz-Valero (MDPI AG, 2024)
There is currently concern about the decrease in physical activity participation among university students. To address this issue, different pedagogical approaches have been developed to improve participants' motivation, with gamification standing out among them. Gamification integrates game design elements into learning environments to increase responsibility, motivation, and engagement in physical activities in different educational stages through intrinsic and extrinsic rewards, although evidence is limited and diverse. Therefore, this study investigates how gamification affects the motivational profile of university students in the context of physical activity. The study was conducted with university students of Physical Activity and Sports Sciences (n = 72), using an experimental design that included a gamified group (GG) and a control group (CG) without gamification. A questionnaire was used to measure motivation before and after the intervention. The results showed a significant increase in intrinsic motivation and a decrease in amotivation in the gamified group, while no significant changes were observed in the control group. However, there were increases in extrinsic motivation in both groups. These findings suggest that gamification can be effective in improving intrinsic motivation and reducing amotivation in university students for physical activity as well as enhancing extrinsic motivation considering the rewards used.